THE EFFECT OF KANGAROO MOTHER CARE ON REDUCING POSTPARTUM DEPRESSION: A SYSTEMATIC REVIEW - Velia Putri Yulias Tanti; Sebayang, Susy Katikana (UNIVERSITAS AIRLANGGA, 2023)
Background: Postpartum depression is a frequent health problem for women during the postpartum period and contribute to maternal morbidity and mortality. Postpartum depression continues to rise with the estimated prevalence in Indonesia is 11.76% in 2021. Kangaroo Mother Care is care for premature babies with skin-to-skin contact between the mother and the baby. Kangaroo Mother Care has been utilized as a non-pharmacological intervention to prevent and reduce the risk of postpartum depression. The aim of the research is to assess the possibility of using Kangaroo Mother Care to reduce the risk of postpartum depression. Method: This was a systematic review study reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Literature was searched in PubMed, Science Direct, Scopus, Sage, and Scilit databases with criteria; article published in 2014–2023, published in English and open access, original research articles, includes postpartum mothers as subjects, includes discussion on the impact of Kangaroo Mother Care on postpartum depression. Exclusion criteria are duplicate articles and articles with titles that do not match the discussion. Result: Six articles that met the inclusion criteria were used in this study. Research and studies were conducted in Indonesia, Spain, and 2 studies in Iran and India. Five studies found that postpartum mothers who carried out Kangaroo Mother Care showed reduction in the risk of postpartum depression, while one study showed the opposite results. Conclusion: Kangaroo Mother Care is effective in reducing postpartum depression in postpartum mothers.